2018
DOI: 10.1016/j.ajpath.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protective Role of Nicotinamide Phosphoribosyltransferase in Acetaminophen-Induced Acute Liver Injury in Mice

Abstract: Acetaminophen overdose is the most common cause of acute liver injury (ALI) or acute liver failure in the United States. Its pathogenetic mechanisms are incompletely understood. Additional studies are warranted to identify new genetic risk factors for more mechanistic insights and new therapeutic target discoveries. The objective of this study was to explore the role and mechanisms of nicotinamide phosphoribosyltransferase (NAMPT) in acetaminophen-induced ALI. C57BL/6 Nampt gene wild-type (Nampt), heterozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Sirtuin activators and their clinical applications are listed in Table 2. [124], Sands et al [125], Krueger et al [126], Venkatasubramanian et al [127] Liu et al [89] Voorhees et al [128], Tesla et al [129], Blaya et al [130], Zhang et al [131],Oku et al [132], Wang et al [133] Abbreviations: AD -Alzheimer's disease, ALS -amyotrophic lateral sclerosis NAD-boosting molecules constitute a newer class of STACs [134]. Since 2003, studies have shown that recycling NAD from nicotinamide by upregulating the NAD remediation pathway can mimic calorie restriction and extend the lifespan of yeast [135].…”
Section: Sirt1 Activators and Their Neuroprotective Effects In Pdmentioning
confidence: 99%
“…Sirtuin activators and their clinical applications are listed in Table 2. [124], Sands et al [125], Krueger et al [126], Venkatasubramanian et al [127] Liu et al [89] Voorhees et al [128], Tesla et al [129], Blaya et al [130], Zhang et al [131],Oku et al [132], Wang et al [133] Abbreviations: AD -Alzheimer's disease, ALS -amyotrophic lateral sclerosis NAD-boosting molecules constitute a newer class of STACs [134]. Since 2003, studies have shown that recycling NAD from nicotinamide by upregulating the NAD remediation pathway can mimic calorie restriction and extend the lifespan of yeast [135].…”
Section: Sirt1 Activators and Their Neuroprotective Effects In Pdmentioning
confidence: 99%
“…We identified 9 NAD metabolism in our screen data (Supplementary Table 5). Additionally, data from our lab suggest overexpression of NAMPT, a gene involved in NAD salvage, is protective against APAP-induced hepatotoxicity in vivo 35 .…”
Section: Resultsmentioning
confidence: 86%
“…RNA-seq data from mice previously published by our lab (GSE110787) evaluating the effect of APAP overdose on RNA expression changes in the liver was 7 male 11 week old C57BL/6 mice, 4 saline treated control mice and 3 mice 24 h after 200 mg/kg APAP (Sigma cat. A7085, St. Louis, MO) exposure via intraperitoneal injection, underwent RNA-sequencing on an Illumina HiSeq 1500 35 . RNA was isolated from liver using the MirVana miRNA isolation kit (Thermo Fisher cat.…”
Section: Methodsmentioning
confidence: 99%
“…The author(s) disclosed receipt of the following financial support for the research, authorship, and/or publication of this article: This study was supported by Science and Technology Bureau of Yuzhong District [2015- [16][17][18][19] and Basic Medical College Research Plan .…”
Section: Author Contributionsmentioning
confidence: 99%